Radiofrequency ablation for liver metastases in patients with gastric cancer as an alternative to hepatic resection - Lee, Jin Won (BMC Cancer, 2017)
BACKGROUND: The purpose of this retrospective study was to determine whether RFA could provide an alternative treatment modality for selected patients who are not candidates for hepatic resection. METHODS: A total of 18 consecutive patients with liver metastases alone from gastric cancer treated with radiofrequency ablation (RFA, n = 11) or hepatic resection (HR, n = 7) at Seoul St. Mary’s Hospital, Korea, between January 2000 and September 2014, were enrolled. RESULTS: The median OS and DFS in the RFA group were 40.5 ± 22.3 and 10.3 ± 1.07 months, respectively. There was no significant difference between the RFA and HR groups in terms of baseline characteristics except for performance status. Mean survival and DFS times of all patients were 60.1 ± 9.4 and 40.9 ± 10.2 months, respectively. Mean OS times in the HR and RFA groups were 67.5 ± 15.4 and 51.1 ± 9.8 months (P = 0.671), respectively, and the mean DFS time in the HR group (74.1 ± 14.2 months) was longer than that in the RFA group (26.9 ± 9.2 months), but the difference was not significant (P = 0.076). CONCLUSIONS: In patients who are not candidates for surgical treatment, RFA may be an alternative to HR.